2022
DOI: 10.3389/fcimb.2022.956445
|View full text |Cite
|
Sign up to set email alerts
|

Genome characterization of a uropathogenic Pseudomonas aeruginosa isolate PA_HN002 with cyclic di-GMP-dependent hyper-biofilm production

Abstract: Pseudomonas aeruginosa can cause various types of infections and is one of the most ubiquitous antibiotic-resistant pathogens found in healthcare settings. It is capable of adapting to adverse conditions by transforming its motile lifestyle to a sessile biofilm lifestyle, which induces a steady state of chronic infection. However, mechanisms triggering the lifestyle transition of P. aeruginosa strains with clinical significance are not very clear. In this study, we reported a recently isolated uropathogenic hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 101 publications
(108 reference statements)
0
7
0
Order By: Relevance
“…Bacterial flagellar biosynthesis is controlled by numerous regulatory systems and the cyclic diguanylate (c-di-GMP) is a global bacterial second messenger that serves as a key modulator connecting flagellar motility to different regulatory pathways in P. aeruginosa and many other microbes ( 35 37 ). Since all the flagellar biosynthetic gene operons were activated by CzcR, we wondered whether flagellar gene expression and swimming motility regulated by CzcR in P. aeruginosa was mediated by the global regulatory signal c-di-GMP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial flagellar biosynthesis is controlled by numerous regulatory systems and the cyclic diguanylate (c-di-GMP) is a global bacterial second messenger that serves as a key modulator connecting flagellar motility to different regulatory pathways in P. aeruginosa and many other microbes ( 35 37 ). Since all the flagellar biosynthetic gene operons were activated by CzcR, we wondered whether flagellar gene expression and swimming motility regulated by CzcR in P. aeruginosa was mediated by the global regulatory signal c-di-GMP.…”
Section: Resultsmentioning
confidence: 99%
“…Quantifications of c-di-GMP in P. aeruginosa strains was performed as described previously with modifications ( 37 ). In brief, P. aeruginosa overnight culture was 1:100 diluted and incubated in LB medium containing 0.5 mM ZnSO 4 or not for 8 h. One mL cell culture was harvested, and cells were lysed with perchloric acid (70% vol/vol).…”
Section: Methodsmentioning
confidence: 99%
“… 41 Previous studies have demonstrated that expression of two genes is effective in increasing and decreasing intracellular c-di-GMP levels in P. aeruginosa , respectively. 36 , 42 Next, β-galactosidase activity assay using the P exsCEBA - lacZ transcriptional fusion showed that the induced transcriptional activity of the exsCEBA promoter in Δ fleR was significantly decreased by expressing the diguanylate cyclase 14945 in the cell ( Figure 4 B). Consistently, both the mRNA and protein levels of ExsA in Δ fleR were reduced to almost WT levels when the diguanylate cyclase 14945 was expressed in the cell ( Figures 4 C and 4D).…”
Section: Resultsmentioning
confidence: 97%
“…For example, P. aeruginosa strains isolated from hospital-acquired pneumonia patients were highly virulent if the isolate harbored the exoU gene compared with isolates that did not ( 36 ). Although exoU gene was known to be a major contributor to potential virulence of P. aeruginosa in terms of cytotoxicity ( 37 , 38 ), in this study, we used comparative genomic analysis to identify the three unique genes, chr_1696 , chr 4238 , and exoU . By gene deletion and virulence screens, we finally confirmed that the exoU gene was the determinant affecting the virulence of P. aeruginosa BSI_S5 at the molecular level by gene deletion studies followed by virulence testing using cell and animal models, beyond a correlation analysis.…”
Section: Resultsmentioning
confidence: 99%